P06.06 Azythromycin treatment for chlamydia trachomatis is associated with vaginal microbiota lacking protective lactobacillus spp. (13th September 2015) - Ma, B; Gajer, P; Humphrys, M; Yang, H; Fu, L; Terplan, M; Bavoil, P; Forney, L; Ravel, J
Abstract : Introduction: Recurrence rate of Chlamydia trachomatis genital infection is frustratingly high ( 25%). While re-exposure is thought to be the main reason. We hypothesised that after and because of azithromycin treatment, the vaginal microbiota is not optimally restored to a protective Lactobacillus spp. dominated state, resulting in enhanced susceptibility to C. trachomatis re-infection. Methods: We characterised the composition, structure and metagenome of the vaginal microbiomes in a cohort of 129 C. trachomatis -positive (CT+) women followed longitudinally before and after azithromycin treatment. We established in vitro susceptibility patterns to azithromycin and doxycycline of vaginal bacteria, including Lactobacillus crispatus, L. iners, L. gasseri, L. jensenii, and Gardnerella vaginalis . Results: Before treatment, CT+ women harbour communities that comprised either a complex assemblage of strict anaerobes, including G. vaginalis, with low proportions of Lactobacillus spp. or a high abundance of L. iners . After azithromycin treatment, we observed an increased proportion of women with communities dominated by high abundance of G. vaginalis and other strict anaerobes, or dominated by L. iners . Antibiotic resistance assays showed that certain types of L. iners and G. vaginalis are highly resistant to azithromycin and to lesser extents to doxycycline. Analysis of L. iners genomes reconstructed from vaginal microbial communities metagenomes showed that multiple phylogenetic clades of L. iners exist. One of these clades is not associated with CT+ women, and is characterised by low number of phage genes as well as unique secondary metabolites gene clusters, all of which could contribute to their resilience. Conclusion: These findings suggest azithromycin treatment is likely to restore a vaginal microbiota with low protective properties, increasing the risk to C. trachomatis re-infection. Disclosure of interest statement: Project funded by NIH-NIAID-STI-CRC U19 AI084044 "Eco-Pathogenomics of Chlamydial Reproductive Tract Infection". No pharmaceutical grants were received in the development of this study.